Engineering Resistance Against Viruses in Field Crops Using CRISPRCas9 - Hinge, Vidya R.; Chavhan, Rahul L.; Kale, Sandeep P.; Suprasanna, Penna; Kadam, Ulhas S. (Current Genomics, 2021)
Food security is threatened by various biotic stresses that affect the growth and production of agricultural crops. Viral diseases have become a serious concern for crop plants as they incur huge yield losses. The enhancement of host resistance against plant viruses is a priority for the effective management of plant viral diseases. However, in the present context of the climate change scenario, plant viruses are rapidly evolving, resulting in the loss of the host resistance mechanism. Advances in genome editing techniques, such as CRISPR-Cas9 [clustered regularly interspaced palindromic repeats-CRISPR-associated 9], have been recognized as promising tools for the development of plant virus resistance. CRISPR-Cas9 genome editing tool is widely preferred due to high target specificity, simplicity, efficiency, and reproducibility. CRISPR-Cas9 based virus resistance in plants has been successfully achieved by gene targeting and cleaving the viral genome or altering the plant genome to enhance plant innate immunity. In this article, we have described the CRISPR-Cas9 system, mechanism of plant immunity against viruses and highlighted the use of the CRISPR-Cas9 system to engineer virus resistance in plants. We also discussed prospects and challenges on the use of CRISPR-Cas9-mediated plant virus resistance in crop improvement.
Keywords: food security